PENGARUH VARIABEL MAKROEKONOMI TERHADAP DANA PIHAK KETIGA PADA BANK KONVENSIONAL DI INDONESIA - Prisilla, Nadila; Munawar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the effect of macroeconomic variables on the collection of third party funds at conventional banks in Indonesia. The data used is monthly time series data from January 2017 to December 2022. The method used in this study is the Vector Autoregression (VAR)/Vector Error Correction Model (VECM) method. However, in choosing between the two methods, stationarity test must be done first. The variables used include inflation, BI rate, crude oil price, and gold price. The results of the study show that the inflation variable has a positive influence, while the BI rate, crude oil price, and gold price variables have a negative influence on third party funds of conventional banks in Indonesia. This research is expected to be applied to banking policy makers with the aim of being insightful to be able to adjust policies when there is instability in macroeconomic variables and for economic policy regulators in determining policies that can stabilize the banking system. In addition, it is used as knowledge for customers to make better decisions regarding investment portfolios with the aim of identifying risks based on macroeconomic conditions.